AS ARTIMANHAS DA MEMÓRIA EM WILSON BUENO - Achre, Simone Pinheiro (2017)
This research deals with the tricks of memory in two books by the Brazilian writer Wilson Bueno (1949-2010). At first, the meaning of the word artimanha (trick) is investigated, followed by a brief biography of the writer. Soon after, a reflection is made on how writing is a mechanism of memory in the book Mano, a noite está velha (2011), by focusing on the writing of the memories of the protagonist, Frederico Souza de Oliveira. Then, the look turns to the presence/absence of Caio Fernando Abreu in Bueno's book. To guide the analysis, the books Mano, a noite está velha (2011) and Morangos Mofados (1995) were approached and traces of daily life and intimacy were read in both narratives. Later, the analysis turns to another book, titled Bolero's Bar (2007), but centers the reading in "Memórias do Caos" present in the second volume, Diário Vagau (2007), both by Wilson Bueno. In these memories, it was noticed that the narrator describes daily life in the same way as the flâneur of Baudelaire (2010). It was verified that the theme that crosses all the analyzes carried out is memory and that the art of good writing is its main trick (artimanha). The main theoretical basis of this research consists of thinkers such as Michel Foucault, Maurice Blanchot, Walter Benjamin and Charles Baudelaire. Through the reflections that emerged from the readings, it was verified that memory is part of the writing itself, because in the act of writing the author does it out of his experiences, reflecting on his practices and also revealing himself. Still, it was noticed that the author becomes a gesture, becomes language and becomes immortal, because he lives in the spaces of the text as an absence/presence. In the end, it was observed that the game of fiction requires a pact between author, text and reader so that the text comes alive and memories do not get lost with the time, so that they generate new lives. Therefore, it can be said that memory is an essential part of writing and reading in Bueno’s books.